Cellulose Nanocrystal Inks for 3D Printing of Textured Cellular Architectures. (7th February 2017) - Siqueira, Gilberto; Kokkinis, Dimitri; Libanori, Rafael; Hausmann, Michael K.; Gladman, Amelia Sydney; Neels, Antonia; Tingaut, Philippe; Zimmermann, Tanja; Lewis, Jennifer A.; Studart, André R.
Abstract : 3D printing of renewable building blocks like cellulose nanocrystals offers an attractive pathway for fabricating sustainable structures. Here, viscoelastic inks composed of anisotropic cellulose nanocrystals (CNC) that enable patterning of 3D objects by direct ink writing are designed and formulated. These concentrated inks are composed of CNC particles suspended in either water or a photopolymerizable monomer solution. The shear‐induced alignment of these anisotropic building blocks during printing is quantified by atomic force microscopy, polarized light microscopy, and 2D wide‐angle X‐ray scattering measurements. Akin to the microreinforcing effect in plant cell walls, the alignment of CNC particles during direct writing yields textured composites with enhanced stiffness along the printing direction. The observations serve as an important step forward toward the development of sustainable materials for 3D printing of cellular architectures with tailored mechanical properties. Abstract : Aqueous and polymer‐based inks with high cellulose nanocrystal (CNC) loading are developed for 3D printing of textured cellular architectures. Alignment of CNC particles within the 3D printed filaments leads to enhanced mechanical properties along the printing direction, akin to wood and other biological composites.